2010
DOI: 10.1002/iub.319
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian ceramide synthases

Abstract: Summary In mammals, ceramide, a key intermediate in sphingolipid metabolism and an important signaling molecule, is synthesized by a family of six ceramide synthases (CerS), each of which synthesizes ceramides with distinct acyl chain lengths. There are a number of common biochemical features between the CerS, such as their catalytic mechanism, and their stucture and intracellular localization. Different CerS also display remarkable differences in their biological properties, with each of them playing distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
487
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 539 publications
(505 citation statements)
references
References 82 publications
16
487
0
2
Order By: Relevance
“…The function of the homeodomain is still unknown [5,9,10,39]. Drosophila schlank encodes the only CerS family member in Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…The function of the homeodomain is still unknown [5,9,10,39]. Drosophila schlank encodes the only CerS family member in Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…growth factors and matrix metalloproteinases [33]. Peptides located at the C-terminus of secreted proteins can be liberated by furin and subsequently gain access to MHC-I in a TAP-independent way [30,32].Previously, we reported the TAP-independent presentation of a C-terminal peptide from the ceramide synthase Trh4, which is a multiple membrane-spanning protein in the ER [34][35][36]. This peptide was the first natural example of a C-terminal processing pathway of ER resident proteins, while previous studies suggested the existence of this route [37][38][39].…”
mentioning
confidence: 99%
“…The CerS2 null mice were generated as described (Levy & Futerman, 2010). The investigation was approved by the local ethics committee, the Institutional Review Board of the Ewha Womans University, and was in accordance with the Declaration of Helsinki, the Animal Care Guidelines of the Ewha Womans University, Medical School, and the National Institutes of Health Guide for the Care and Use of Laboratory Animals.…”
Section: Methodsmentioning
confidence: 99%
“…C6‐Ceramide also inhibited voltage‐gated K + currents and induced vasoconstriction in rat and human pulmonary arteries (Moral‐Sanz et al ., 2011). Ceramide, the backbone of all complex SLs, is synthesized by the N ‐acylation of a sphingoid long‐chain base by a family of six ceramide synthases (CerS; Levy & Futerman, 2010), each generating ceramides with a different acyl chain length. C18‐ceramide is generated by CerS1 and CerS4, and C16‐ceramide is generated by CerS5 and CerS6.…”
Section: Introductionmentioning
confidence: 99%